THE EFFECT OF ENTREPRENEURIAL LEARNING TO ENHANCE ENTREPRENEURIAL INTENTION FOR STUDENTS UNIVERSITY: THE MEDIATING ROLE OF ONLINE SOCIAL NETWORK - Yusni Arni, (JOEL: Journal of Educational and Language Research, 2023)
This study aimed to investigate entrepreneurship learning in universities regarding the effect of achievement motivation and creativity on student entrepreneurial interests mediated by online social networks. Various private universities in Lampung province collected data from 225 respondents online. The data were analyzed using the structural equation model Smart Pls 3.2.4. this study investigated seven research hypotheses in this study. The result of the research shows that achievement motivation and creativity have a significant effect on entrepreneurial interest. The results also show that online social networking can mediate the relationship between achievement motivation and creativity on entrepreneurial interest. The findings of this study also contribute to the conceptual framework for lecturers in entrepreneurship learning to increase student entrepreneurship interest. It is recommended to compare the entrepreneurial interest model among state universities as a comparative study to understand how to build entrepreneurial interest in universities as a contribution to creating young entrepreneurs